Contribution of Gender on Academic Self-Concept among Adolescents of Children Villages, Nepal - Dangol, Rita (International Journal of Social Sciences and Management, 2019)
Academic self-concept is the crucial part of the educational adjustments of adolescents. Thus this paper aims to assess the academic self-concept via gender of adolescents. For this purpose, researcher employed the post positivist philosophy with cross sectional survey design. The data was gathered through self-administered questionnaire from the 74 adolescents. This numbers of adolescent were randomly assigned from 95 adolescents according to the Wolff and Pant’s guidelines. After this, the researcher adopted both descriptive and Chi square test to analyze the results. This study revealed that the adolescents’ exhibit the elevated level of academic self-concept where their peer groups, teachers, school and families also make contribution. Likewise, gender makes significant effects in academic self-concept and exam results among adolescent. Finally, the academic self-concept makes sure about the well educational adjustment among adolescents and further promotes their successful career in near future.